Stability of Perovskite Solar Cells - ALEX FAN, XU (My University, 2020)
Organic−inorganic hybrid perovskite solar cells (PSC) have been widely considered as a promising candidate for the next generation of photovoltaics (PV). The power conversion efficiency of a single junction PSC has achieved a maximum of 25.5% within only one decade, rivaling traditional PV technologies. While PSCs inspired a new era for photovoltaic development, they exhibited severe instability problems, thereby impeding their commercialization. Thus, the main projects in this thesis are to improve stability of PSCs. To enhance the intrinsic stability of PSC, a hydrophobic five-membered ring cation is introduced to replace the unstable protype methyl-ammonium (MA) cation. In Chapter 2, the crystal structure of the new perovskite material, (C4H8NH2)PbI3 (PyPbI3) is determined and illustrated by single crystal X-ray diffraction. UV absorption spectra, steady state photoluminescence and XRD results show it is a promising alternative to hybrid organic–inorganic perovskites due to its good water resistance and suitable bandgap. The MA-based perovskites are unstable at high temperature or under moisture attack. To overcome this barrier, both thermal stability and water resistance of PyPbI3 are investigated in Chapter 3. It presents not only prolonged moisture resistance up to 4 months in ambient conditions and a favorable bandgap of 1.80 eV, as determined by P-XRD and UV absorption, but also excellent thermal stability, as verified via the in situ thermal XRD technique. The phase stability of PyPbI3 is investigated in Chapter 4. The hybrid perovskite was synthesized successfully via a simple drop casting method. It presents not only excellent phase stability, but also low trap-state density, as confirmed via XRD and space-charge-limited currents measurements. The results indicate that Py-based perovskite is environmentally stable. The commonly employed formamidinium (FA)-containing PSCs exhibit a severe phase instability problem. Here in Chapter 5, both phase stability and energy efficiency of FA-based PSCs are improved by treating the perovskite surface with pyrrolidinium hydroiodide (PyI) salts, resulting in a 1D perovskite structure (PyPbI3), stacked on the original 3D perovskite. By employing in situ XRD measurements, we revealed that the temperature-dependent phase transition activation barrier was enhanced after forming the 1D/3D structure, resulting in a prolonged transition time by 30−40-fold. From the first-principle calculations, we found the thermodynamic energy difference between two phases reduced from −0.16 to −0.04 eV after the stacking of 1D PyPbI3, offering additional lifetime improvement. Moreover, the champion 1D/3D bilayer PSC exhibits a boosted power conversion efficiency of 19.62%, versus 18.21% of the control. Such 1D/3D bilayer structure may be employed in PSCs to enhance their phase stability and photovoltaic performance.